What Drives Adolescent Sexual Behavior in Dormitories: Freedom or Influence? - Indraswari, Ratih; Handayani, Novia; Kusumawati, Aditya (Universitas Airlangga, 2025)
Background: Similar to teenagers his age, teenagers who live in dormitories also experience sexual attraction and are curious to try new things. Purpose: This study aims to investigate the sexual behavior of adolescents living in dormitories. Methods: The cross-sectional method was used on 147 students using the proportionate random sampling technique. The dependent variable in this study is pupils’ characteristics (sex, age, and puberty status), while the independent variable is the behavior of pornography consumption (content, context, onset, frequency, media, duration, reason, and peer influence). The data obtained were then analyzed by univariate and independent sample t-tests. Results: Most of the respondents in this study were women (77.6%), aged 19-26 years (71.4%), and diploma graduates (53.7%). There is no correlation between knowledge and attitude about reproductive health toward practicing sexual behavior among adolescents in dormitories. Age and education are related to adolescents' knowledge about reproductive health, while gender affects adolescents' practices in sexual behavior. Conclusion: It suggests improving adolescents’ skills to resist pressure from peers and boy/girlfriends. It is needed to create a safe and supportive environment for adolescent development. A well-rounded educational program should include information about reproductive health, healthy relationships, and communication in relationships. Joint efforts from parents, educators, and the community are needed to create a safe and supportive environment for adolescent development.